ANALISIS PERILAKU BIAYA TERHADAP MAHASISWA - Laksamana, Candra; Nur Fahira, Dinda; Widya Putri, Wika (Research in Accounting Journal (RAJ), 2021)
The purpose of this study is to analyze the allocation of costs spent by a student for his needs through an accounting perspective. The benefit of this research is that every individual can overcome life problems, which are mostly related to material or resources. When individuals are faced with various offers from the surrounding environment, then they must be able to react by determining the profit and loss through cost analysis to be able to survive. In this study using the interview method in data collection and grouping into two parts including student students and students who do not work. The results of the analysis of the cost grouping can be seen that the highest average costs incurred are secondary costs, followed by primary costs and finally tuition fees. Where secondary costs are costs incurred for entertainment such as watching, playing, hageout, and others. Primary costs are costs incurred for the basic needs of students such as books, fuel, make-up and others. And tuition fees are costs incurred to pay one semester tuition.